Potential contribution of using voluntary agreements to manage informal sector pollution in Zambia : the case of Lusaka's Soweto and City markets - Mungatana, Eric D. (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2012.